Features of Thermal Conductivity of Composites Based on Thermoplastic Polymers and Aluminum Particles - R.V. Dinzhos; E.A. Lysenkov; N.M. Fialko (Журнал нано- та електронної фізики)
The results of the experimental studies and theoretical analysis of thermal conductivity of composites based on thermoplastic polymers and aluminum particles are presented. It is revealed that the studied systems exhibit percolation behavior. It is established that for composites filled with aluminum particles the double percolation effect is observed. A combined percolation model which very accurately describes the concentration behavior of thermal conductivity and takes into account two percolation transitions is offered.